2016
DOI: 10.1371/journal.ppat.1005755
|View full text |Cite
|
Sign up to set email alerts
|

A Homolog Pentameric Complex Dictates Viral Epithelial Tropism, Pathogenicity and Congenital Infection Rate in Guinea Pig Cytomegalovirus

Abstract: In human cytomegalovirus (HCMV), tropism to epithelial and endothelial cells is dependent upon a pentameric complex (PC). Given the structure of the placenta, the PC is potentially an important neutralizing antibody target antigen against congenital infection. The guinea pig is the only small animal model for congenital CMV. Guinea pig cytomegalovirus (GPCMV) potentially encodes a UL128-131 HCMV PC homolog locus (GP128-GP133). In transient expression studies, GPCMV gH and gL glycoproteins interacted with UL128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
182
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(189 citation statements)
references
References 105 publications
6
182
1
Order By: Relevance
“…It has been well established for HCMV that, while gB is an important target of neutralizing antibodies, the majority of neutralization activity in seropositve individuals is directed against the gH/gL/ UL128-131A pentameric complex (47,48). Furthermore, the pentameric complex has also been shown to be a target of neutralizing antibodies for guinea pig CMV (49). In this study, we determined that antibodies targeting both RhgB and RhPC contribute to the total neutralization activity of RhCMV-seropositive monkey sera in approximately equivalent proportions (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established for HCMV that, while gB is an important target of neutralizing antibodies, the majority of neutralization activity in seropositve individuals is directed against the gH/gL/ UL128-131A pentameric complex (47,48). Furthermore, the pentameric complex has also been shown to be a target of neutralizing antibodies for guinea pig CMV (49). In this study, we determined that antibodies targeting both RhgB and RhPC contribute to the total neutralization activity of RhCMV-seropositive monkey sera in approximately equivalent proportions (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The high-potency-infused animals were sampled at days 0, 1, 2, 3,4,7,10,14,21,28,35,42,49,56,63,70,77, and 84. Amniotic fluid (by amniocentesis), urine (by clean pan collection), and saliva (by oral saline wash), were also collected on all animals on a weekly to biweekly intervals until fetal harvest.…”
Section: Methodsmentioning
confidence: 99%
“…In GPCMV, a homologous UL128-131 locus has been identified, and the ability to form a pentameric complex has been investigated (28,58). We recently demonstrated that this complex is important for virus tropism to epithelial cells, pathogenicity, and congenital infection (103). Importantly, the homolog pentameric complex is highly immunogenic (102).…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine strategy was successful in fully preventing pup deaths and greatly reduced the level and incidence of pups with congenital CMV infection compared to a nonvaccinated control group. This promising vaccine strategy presents potential opportunities for improvement via the inclusion of the homolog pentameric complex, which is considered an important complex for virus infection of epithelial cells (103) and a variety of other cell types. The potential addition of neutralizing antibodies to this complex will greatly reduce congenital transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation